Teilhard and the future of humanity - Meynard, Thierry (Fordham University Press, 2006)
Bringing together original essays by experts who reflect on the French scientist and Jesuit Pierre Teilhard de Chardin's legacy for the globalized world, this book explores such topics as the idea of God and the person, quantum reality and Teilhard's vision, spiritual resources for the future, and much more.